#### Answer

$-7$

#### Work Step by Step

$4^{x-2}=2^{3x+3}\Rightarrow \left( 2^{2}\right) ^{x-2}=2^{3x+3}\Rightarrow 2^{2x-4}=2^{3x+3}\Rightarrow 2x-4=3x+3\Rightarrow x=-7$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$-7$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.